Impact of financial literacy on investment decisions: evidence from individual investors in Jaffna district - Balagobei, S.; Prashanthan, V. (University of Jaffna, 2021)
Financially literate individual investors can make smart investment decisions over complex financial scenarios to boost their financial wealth. The aim of the study is to investigate the influence of financial literacy on investment decisions of individual investors in Jaffna district. Further this study explores the impact of financial knowledge, financial behavior and financial attitude on investment decisions of individual investors. Two hundred individual investors in Jaffna district were selected as sample by using random sampling technique and primary data was collected through a structured questionnaire. Financial literacy consists of three dimensions namely financial knowledge, financial behaviour and financial attitude whereas investment decisions are measured by accounting information, self/firm-image coincidence, advocate recommendations and personal financial needs. Data was analyzed using the techniques of correlation, regression, t-test and ANOVA. The results reveal that financial literacy significantly positively impacts on investment decisions of individual investors in Jaffna district. The findings recommend the necessity for effective financial literacy programs focusing especially on enhancing financial knowledge, behaviors and attitude to facilitate informed investment decisions of individual investors.
Keywords: Financial Literacy; Financial knowledge; Financial behavior; Financial attitude; Investment decisions